Impact of Big Data Analytics on Firm Risk in Financial Sector Companies - Rizka Alazani; Erni Masdupi (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to examine the effect of Big Data Analytics on firm risk in financial sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period, with control variables including firm age, leverage, and Return on Assets. The study adopts an explanatory quantitative approach using an unbalanced panel dataset derived from annual reports and stock price data, comprising a total of 197 observations. Big Data Analytics is measured through content analysis, while firm risk is proxied by the standard deviation of daily stock returns. Data analysis is conducted using panel data regression with the Fixed Effect Model, which is further corrected using Generalized Least Squares to address heteroskedasticity issues, with the assistance of EViews 13 software. The results indicate that Big Data Analytics has a positive and significant effect on firm risk. This finding suggests that higher adoption of Big Data Analytics encourages firms to engage in more complex and aggressive strategic decision-making, which in turn increases performance volatility and overall risk exposure.